(untitled) (Bangladesh Journal of Physiology and Pharmacology, 2015)
Aim The study aims at determining the possible effects of Carica papaya leaf juice and hydrocortisone in increasing the platelet count in thrombocytopenia similar to dengue fever. Methodology The study was carried out on 24 Long Evans Norwegian strain healthy rats to investigate the comparative platelet increasing effect of Carica papaya leaf juice and hydrocortisone in experimentally induced thrombocytopenic rats. Thrombocytopenia was induced by 3 doses of cyclophosphamide (100mg/kg body weight) given subcutaneously. The rats were divided into 4 groups comprising of six animals in each group. These groups included a normal control and a cyclophosphamide induced thrombocytopenic control and the remaining two cyclophosphamide induced thrombocytopenic groups were administered Carica papaya leaf juice and hydrocortisone respectively. The duration of study was 15 days. The clotting time was determined on the 15th day although blood samples were obtained from the rat tails at various time intervals to determine the platelet count. Collected data was tabulated and Statistical analysis was performed by using appropriate significant test. A probability value P < 0.05 was considered to be statistically significant. Result Average platelet counts of the test and control groups were (6.89)×105/?L and (6.75)×105/?L respectively before the experiment. In the experiment there was no significant difference in the platelet counts during the first 3 days in either group. However, platelet counts within the test group started to fall after Day 3 and remarkable thrombocytopenia developed after 7days and the average value was (2.68)×105/?L. From day 11 Carica papaya leaf juice and Hydrocortisone was given in two test groups following cyclophosphamide and platelet counts observed to reach a peak level at Day 14 (7.83)×105/?L in case of following Carica papaya leaf juice, and (4.05)×105/?L in case of following Hydrocortisone. The clotting time was determined on day 15 and it was found to be considerably lower (95.5 ± 2.762 sec) in case of Carica papaya leaf juice than (129±3.124 sec) in Hydrocortisone. Conclusion Carica papaya leaf juice has more platelet increasing effect than hydrocortisone and this study also reflects that Carica papaya leaf juice may be a potential candidate for further research leading to the development of a herbal therapeutic agent for thrombocytopenia manifested in diseases such as dengue. DOI: http://dx.doi.org/10.3329/bjpp.v30i2.22681 Bangladesh J Physiol Pharmacol 2014; 30(2): 32-40